A Retrospective Evaluation of the use of Thiazolidinediones in Patients with Diabetes Mellitus in a Private Hospital in Ras Al Khaimah - F, Smitha; R, Padma; SK, Multani; J, Meenakshi (Indian Journal of Pharmacy Practice)
Diabetes Mellitus is a major public health problem affecting around 800,000 people of United Arab Emirates (about 19.2 per cent of the th population). Thus the country is ranked as the 10 worldwide in terms of highest prevalence rate as per the latest reports of the International Diabetes Federation. Thiazolidinediones (Rosiglitazone and Pioglitazone) are a group of antidiabetic drugs which are commonly used in United Arab Emirates among diabetic patients. There are reports about the cardiovascular risks and hepatotoxic effects of thiazolidinediones. Hence the present study was undertaken. The aim of the study was to determine the incidence of thiazolidinedione usage, its adverse drug reactions, efficacy and safety in diabetic patients. The present study was undertaken after the approval of the Research and Ethics Committee of RAK Medical and Health Sciences University. This was a retrospective study conducted in the outpatient clinic of the Department of Endocrinology and Diabetes of a private hospital in Ras Al Khaimah, United Arab Emirates, between January to December 2008. The required data was collected from the selected patients and entered into specific patient proforma. The data was analyzed for the following parameters like incidence of usage of thiazolidinediones, its efficacy and adverse drug reactions. A total of 143 patients with diabetes were enrolled in the study, out of which 54 patients were on Thiazolidinediones- 48 on Rosiglitazone and 6 on Pioglitazone- in the beginning of the study. At the end, 73 patients were on Rosiglitazone and 17 were on Pioglitazone. The most commonly observed adverse effect was pedal edema. No cardiovascular risks were observed in any of the patients who were on either Rosiglitazone or Pioglitazone. Though there are reports of cardiovascular risks with Thiazolidinediones, throughout our study, none of the patients reported any cardiovascular risk.
Keywords: Diabetes Mellitus; Thiazolidinediones; Adverse drug reactions; Utilization evaluation